Glycolipid-Mediated Basophil Activation in Alpha-Gal Allergy - Iweala, Onyinye I. (J Allergy Clin Immunol, 2020)
Alpha-gal-containing glycolipids activate basophils sensitized with plasma from alpha-gal allergic subjects in an IgE-dependent manner suggesting a role for glycolipid in the effector phase of IgE-mediated food allergy.